Problem-Based Learning Model Integrated with Metacognitive Approach Through Flipped Learning in Science Learning Lectures - Gamar Abdullah; Abdul Haris Panal (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2022)
Problem-Based Learning model through a metacognitive approach is one thing that is assumed to be appropriate during the Covid-19 Pandemic. One of the online learning methods is flipped learning. In this study, the application of PBM through a metacognitive approach is integrated with the implementation of flipped learning. This study aims to describe the implementation of an integrated problem-based learning model with a metacognitive approach through flipped learning in science learning lectures. This research is a development research using the Borg and Gall model with the research subjects being PGSD students of the Faculty of Education, State University of Gorontalo who actively participate in science learning lectures. Based on the results of the study, it can be described that the PBL model integrated with the metacognitive approach through flipped learning can provide a new learning experience for students. Flipped learning requires students to study basic material before the lecture takes place so that during lectures, students can spend their time applying the material through active learning and problem solving. The integration of the problem-based learning model integrated with the metacognitive approach through flipped learning restructures the lecturer-centered learning approach and makes students the center of learning.